Characterization of the phenotype with cognitive impairment and protein mislocalization in SCA34. (April 2020) - Beaudin, Marie; Sellami, Leila; Martel, Christian; Touzel-Deschênes, Lydia; Houle, Gabrielle; Martineau, Laurence; Lacroix, Kevin; Lavallée, Andréane; Chrestian, Nicolas; Rouleau, Guy A.; Gros-Louis, François; Laforce, Robert; et al.
Abstract : Objective: To better characterize the neurologic and cognitive profile of patients with spinocerebellar ataxia 34 (SCA34) caused by ELOVL4 mutations and to demonstrate the presence of ELOVL4 cellular localization and distribution abnormalities in skin-derived fibroblasts. Methods: We investigated a 5-generation French-Canadian kindred presenting with a late-onset cerebellar ataxia and recruited age- and education-matched controls to evaluate the presence of neurocognitive impairment. Immunohistochemistry of dermal fibroblasts derived from a patient's skin biopsy was performed. Results: Patients had a late-onset slowly progressive cerebellar syndrome (mean age at onset 47 years; range 32–60 years) characterized by truncal and limb ataxia, dysarthria, hypometric saccades, and saccadic pursuits. No patient had past or current signs of erythrokeratodermia variabilis, which had previously been reported. MRI revealed cerebellar atrophy, with pontine atrophy (4 of 6 patients), and cruciform hypersignal in the pons (2 of 6 patients). Fluorodeoxyglucose-PET showed diffuse cerebellar hypometabolism in all 5 tested patients with subtle parietal hypometabolism in 3. Significant cognitive deficits were found in executive functioning, along with apparent visuospatial, attention, and psychiatric involvement. Immunohistochemistry of dermal fibroblasts showed mislocalization of the ELOVL4 protein, which appeared punctate and aggregated, supporting a dominant negative effect of the mutation on protein localization. Conclusions: Our findings support the pathogenicity of ELOVL4 mutations in cerebellar dysfunction and provide a detailed characterization of the SCA34 phenotype, with neurocognitive changes typical of the cerebellar cognitive-affective syndrome.